(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study aims to record and analyze the ongoing construction process of Toba Batak traditional houses in Samosir Regency in 2025 as part of the Indonesian architectural heritage. The approach used is descriptive qualitative with a case study method through field observations, visual documentation, in-depth interviews, and literature review. The results show that the construction process of Toba Batak traditional houses still maintains traditional construction stages, wooden structural systems, and nailless connection techniques passed down through generations, although there are adjustments to current conditions. The construction process functions not only as a construction activity but also as a cultural practice that embodies customary values, local knowledge, and social togetherness. This study confirms that Toba Batak traditional houses constitute a dynamic architectural heritage, where building traditions remain alive and relevant amidst changing times. Documentation of this construction process is expected to support efforts to preserve and develop knowledge of Indonesian architectural knowledge sustainably.